Effect of Rural Banditry on Food Security and Poverty Reduction in Nigeria - Nwankpa, Nneka (European Journal of Sustainable Development, 2024)
This research investigates how rural banditry hinders sustainable food security and poverty reductions in Nigeria. The Food and Agricultural Organisation, the International Monetary Fund, the National Bureau of Statistics, the United Nations Development Programme, scholarly journals, and field surveys were the sources from which the data were gathered. Three hundred questionnaires were administered to farmers in six states via Plateau, Nassarawa, Kaduna, Benue, Oyo and Niger, in addition to a focused group discussion with selected farmers in each of the study areas. Data collected were analyzed using descriptive and inferential statistics. Findings show that unemployment, poverty, poor governance, inadequate infrastructure, insufficient security measures and lack of effective institutional coordination, create a network of individuals who support or engage in banditry; farmers experienced disruptions in farming activities, psychological distresses and loss of livestock. Among the socio-economic impacts of banditry include: loss of income and economic opportunities, displacement and migration of the rural population, reduced productivity and infrastructural degradation. These led to food shortages, hikes in food prices, malnutrition and increased poverty level in Nigeria. This study emphasizes the urgent need by the federal and state governments to tackle the problems of unemployment and poverty; develop infrastructure; increase security expenditure; and implement targeted rural development policies. These solutions will curb rural banditry, ensure food security and reduce poverty in Nigeria. Keywords: Rural Banditry, food security, poverty reduction, food production, development policies, farmers.